2022
DOI: 10.3390/microorganisms10020325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inoculation Level on the Impact of the PGPR Azospirillum lipoferum CRT1 on Selected Microbial Functional Groups in the Rhizosphere of Field Maize

Abstract: The impact of inoculated plant growth-promoting rhizobacteria (PGPR) on its host physiology and nutrition depends on inoculum level. Whether the impact of the inoculated PGPR on the indigenous rhizosphere microbiota also varies with the PGPR inoculum level is unclear. Here, we tested this issue using the PGPR Azospirillum lipoferum CRT1—maize model system, where the initial seed inoculation is known to enhance maize growth and germination, and impacts the maize rhizomicrobiota, including microbial functional g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 64 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…The inoculation of maize with Azospirillum brasilense did not affect the specific rhizobacterial community [30]. In contrast, the inoculation with Azospirillum lipoferum CRT1 significantly impacted the total bacterial community in maize fields [31]. Changes in the microbial community resulting from Azospirillum inoculation have not yet been reported for other plant species.…”
Section: Impact Of Azospirillum Inoculation On Fieldsmentioning
confidence: 79%
“…The inoculation of maize with Azospirillum brasilense did not affect the specific rhizobacterial community [30]. In contrast, the inoculation with Azospirillum lipoferum CRT1 significantly impacted the total bacterial community in maize fields [31]. Changes in the microbial community resulting from Azospirillum inoculation have not yet been reported for other plant species.…”
Section: Impact Of Azospirillum Inoculation On Fieldsmentioning
confidence: 79%
“…Cluster B, consisting of Skermanella, Flavisolibacter, and Microvirga, exhibited strong positive correlations with fresh weight (FW), dry weight (DW), and nitrogen (N), phosphorus (P), and potassium (K) content. This cluster comprises beneficial microorganisms such as Skermanella, a diazotroph commonly found in soil and reported as a biological control agent [76,77]; Flavisolibacter, a PGPR phosphate solubiliser and indole-3-acetic acid (IAA) producer [78]; and Microvirga, a nitrogen-fixing bacterium [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Herschkovitz et al (2005) have demonstrated that A. brasilense did not alter or disrupt the microbial system on maize field at the group-specific level. However, Renoud et al (2022) demonstrated that Azospirillum lipoferum CRT1 inoculation significantly impacted the total bacterial community in the three evaluated fields, but only with the reduced formulation. Few studies have demonstrated the effect of native microbial community on Azospirillum spp.…”
Section: Introductionmentioning
confidence: 87%